2020
DOI: 10.1016/j.addbeh.2019.106116
|View full text |Cite
|
Sign up to set email alerts
|

Cue salience of the use of an electronic nicotine delivery system (ENDS) device marketed to women

Abstract: Introduction-Passive exposure to the use of electronic nicotine delivery systems (ENDS or ecigarettes) has been shown to generalize as a smoking cue. As young adult women in particular are increasingly targeted by ENDS distributors, the present study examined whether passive exposure to the use of a female-marketed ENDS product selectively enhanced smoking urge, cigarette and e-cigarette desire, and smoking behavior among women (vs men) smokers.Methods-Using a mixed design, young adult smokers (n=64; mean age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…79 , 82 In regards to nicotine content, only 10 studies reported the ENDS nicotine levels used in their experiments. 64 , 69 - 72 , 74 , 77 , 79 - 81 E-liquids nicotine content ranged from 0 to 59 mg/ml (salt). Further information about ENDS types and nicotine levels used in the reviewed studies, including related outcomes, is presented in the sub-sections below and in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…79 , 82 In regards to nicotine content, only 10 studies reported the ENDS nicotine levels used in their experiments. 64 , 69 - 72 , 74 , 77 , 79 - 81 E-liquids nicotine content ranged from 0 to 59 mg/ml (salt). Further information about ENDS types and nicotine levels used in the reviewed studies, including related outcomes, is presented in the sub-sections below and in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Overall, the reviewed studies were carried out between 2012 and 2020 and most of them used for their experiments, first- and second-generation ENDS. Only two studies used exclusively third generation, 71 , 72 and one study reported using fourth generation ENDS (JUUL) as a cue. Thus, two studies 65 , 66 directly compared first and third generation ENDS and their respective effects on craving.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations